Orientalism and its Critics - Halliday, Fred (Jama’a: an Interdisciplinary Journal of Middle East Studies, 1998)
Fred Halliday examines the controversial debate triggered by Edward Said’s Orientalism. Adopting a somewhat detached position toward the various approaches in the debate, Halliday introduces the mainstays of Said’s work along with its various critiques. Halliday traces what he views as the roots of the debate: how should one evaluate writing on Middle Eastern societies in particular and the methodology in social analysis in general. On the methodological level, Halliday defines the options of social analysis: a traditional, linguistically, and culturally- based approach derived from classical studies on the one hand, and a critical approach to writing and discourse derived from post- modernism on the other.